Efek Penambahan Taping pada Intervensi Micro Wave Diathermy dan Stretching Terhadap Pengurangan Nyeri pada Kondisi Plantar Fascitis (Lembaga Penerbitan Universitas Esa Unggul, 2009)
This Researh aims to detect increasing effect difference existence taping in intervention micro wave mengathermy (mwd) and stretching towards pain reduction in condition plantar fasciitis. method: This research kind quation eksperimental to detect effect a intervention that done towards watchfulness object. Sample is grouped to be two treatment groups, my treatment group consists of 7 person with interventions that given micro wave mengathermy (mwd) and stretching and treatment group ii that consist of 7 person with interventions that given increasing taping in intervention micro wave mengathermy (mwd) and stretching. This watchfulness statistics analysis uses test wilcoxon and man-whitney. Result: with test wilcoxon match pairs in my treatment group demoes value p = 0,018 (p<? =0,05) and in treatment group ii value p = 0,018 (p<? =0,05) mean intervention that done in each group berefek in pain reduction in condition plantar fasciitis. and result mann-whitney demo value p = 0,003 p<? =0,05 that mean there effect significant between my treatment group and treatment group ii. Conclusion: there increasing effect difference taping in intervention micro wave mengathermy and stretching towards pain reduction in condition plantar fasciitis.Keywords: Tapping, Plantar Fascitis, Stretching